1987
DOI: 10.3109/07435808709035464
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine (TegretolR) Inhibits in Vivo Iodide Uptake and Hormone Synthesis in rat Thyroid Glands

Abstract: Decreased serum concentrations of T3 and T4 occur in patients treated with the anticonvulsant drug carbamazepine (CBZ), but with rare exception, these patients remain euthyroid. The mechanism that accounts for diminished hormone levels is unknown, and our objective was to study the direct effect of CBZ on iodide uptake and hormone synthesis in thyroid glands of CBZ-treated and pair-fed control rats. Chronic ingestion (per os) of CBZ in male rats reduced the four hour thyroid 131I-iodide uptake by approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…[ 16 17 ] In addition, study done by Villa and Alexander also suggested that iodine uptake inhibition by the thyroid gland might be one of the other mechanism by which carbamazepine can induce thyroid dysfunction. [ 18 ] Although mechanistic approach based study was not conducted, the present study showed screening for thyroid hormones is recommended for patients periodically taking long-term conventional AEDs than for the newer drugs, thereby thyroid dysfunction induced complications can be prevented in the epileptic patients. The small sample size was the limitation in our study; therefore, further prospective studies are required to be mediated on a larger scale of adult epileptic patients to confirm our results.…”
Section: Discussionmentioning
confidence: 88%
“…[ 16 17 ] In addition, study done by Villa and Alexander also suggested that iodine uptake inhibition by the thyroid gland might be one of the other mechanism by which carbamazepine can induce thyroid dysfunction. [ 18 ] Although mechanistic approach based study was not conducted, the present study showed screening for thyroid hormones is recommended for patients periodically taking long-term conventional AEDs than for the newer drugs, thereby thyroid dysfunction induced complications can be prevented in the epileptic patients. The small sample size was the limitation in our study; therefore, further prospective studies are required to be mediated on a larger scale of adult epileptic patients to confirm our results.…”
Section: Discussionmentioning
confidence: 88%
“…TSH responses to TRH are normal in patients taking CBZ, and therefore pituitary interference by the drug seems unlikely (1,5). It has also been suggested that CBZ may inhibit iodine uptake by the thyroid gland (25).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism was supported by Surks et al who postulated the drug-induced inhibitory response of thyroid releasing hormone on TSH release [21]. Villa and Alexander proposed another mechanism for carbamazepine induced thyroid dysfunction due to the inhibition of iodine uptake by the thyroid gland [22].…”
Section: Discussionmentioning
confidence: 89%